Management of fishery resources in the Gulf of Nicoya, Costa Rica; Methods and preliminary results - Stevenson, David K. (1978)
Coastal tropical fishery resources are commonly harvested from small vessels with relatively unsophisticated gear such as hand lines, traps and nets. Although these artisanal fishing practices are not as productive, on a per unit basis as those used in more advanced temperate zone fisheries, substantial fishing effort is nonetheless generated by the magnitude of operating units. Available resources may, in many cases, be overexploited. The successful development of tropical artisanal fisheries requires that appropriate management measures be applied so that maximum harvests may be sustained without depleting resources.